Analysis of Transparency and Public Participation in the Selection Process of the Sub-district Election Supervisory Committee in the General Election Supervisory Agency of Bandung City in 2022 - Fahmy Iss Wahyudy (Epistemik Press, 2023)
The General Election Supervisory Agency (Bawaslu) is the most advanced mode of election supervision institutions, high public demands for the implementation of honest and fair elections pave the way for several improvements and strategic functions owned by The General Election Supervisory Agency (Bawaslu). With such strategic authority, which includes supervision, prevention, and enforcement of violations in elections, The General Election Supervisory Agency (Bawaslu) is required to have qualified human resources, especially at the grassroots level as the front line of election supervision. To fulfill these obligations, the General Election Supervisory Agency Regulation (Perbawaslu) Number 8 of 2019 was prepared as a reference in the selection and recruitment process for Election Supervisors. The selection of Bandung City cannot be separated from political complexity and some preliminary findings related to the issue of transparency and participation during the selection process. This research uses a descriptive qualitative approach with a case study method. A series of in-depth interviews and relevant literature studies were conducted to meet data needs during the study. The results of this study show that the selection process for Sub-district Election Supervisory Committee (Panwaslu Kecamatan) is still plagued by several problems, especially the carrying capacity of the budget and the relatively short preparation time. Meanwhile, in the aspect of transparency, the entire selection process supervised by the working group seems to display several positive things, including efforts to publish all selection results through various information media, both print and digital-based. Even though public participation in the context of registering as a candidate for Sub-district Election Supervisory Committee (Panwaslu Kecamatan) members is far beyond the declared target, there are still problems that can be corrected, especially regarding the distribution of the number of applicants and the representation of 30% women in the entire selection stage that has not been met.